Komunikasi Pembangunan Partisipasi Membangun Objek Wisata Terhadap Peningkatan Ekonomi Masyarakat - Idawati (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Community participation in building tourism objects is one form of improving the economic welfare of the community, so that people have a better standard of living in the future. The city of Dumai is an industrial city known for its beautiful beaches, as an industrial city, of course the government through a program to touch people with advanced thinking patterns to build local tourism that they have with quite beautiful beach views. This study aims to find out how community participation is to build natural tourism objects to improve the economy. And what are the barriers to community participation. The theoretical approach used is the theory of